A hedonic price study on warm- and cold-water shrimp in danish retail sale. Issue 1 (2nd January 2020) - Hukom, Venticia; Nielsen, Max; Ankamah-Yeboah, Isaac; Nielsen, Rasmus
Abstract: The ever-growing industry of farmed warm-water shrimp in developing countries claims the continued expansion of export markets in developed countries, where they form a growing share of markets traditionally supplied by wild-caught shrimp. In this market transition, developing countries can benefit from knowledge regarding the consumer valuation of shrimp attributes to reasonably target product forms. In this article, the implicit price for the intrinsic and extrinsic product attributes of shrimp purchases from 2011–2015 scanner data is analyzed in Danish retail sales using a hedonic price model. For intrinsic attributes, the results show that a price premium exists for warm-water shrimp and has a larger impact on low-income households. Freshness creates a price premium for warm-water shrimp, but cold-water shrimp faces price discounts. For extrinsic attributes, private labels lead to a price premium for warm-water shrimp. This article shows that despite traditionally eating wild-caught cold-water shrimp, Danish consumers are willing to both purchase and pay a price premium for warm-water shrimp. The findings also indicate that exporters and supermarket chains together can benefit from using private labels. Therefore, the warm-water shrimp farmers have the potential to export to this market, which traditionally has been dominated by cold-water shrimp consumption.